Pengaruh Brand Trust Dan Celebrity Endorser Terhadap Keputusan Pembelian Smartphone Samsung Pada Konsumen Di Surya Phone Lamongan - Dian Eka Permata Sari; Nur Hidayati; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this study was to determine how the influence of brand trust and celebrity endorser on purchasing decisions. This research was conducted on Samsung smartphone consumers in Surya Phone Lamongan with a sample of 45 respondents. The research method used is non-probability sampling with accidental sampling technique. The data used from the results of distributing questionnaires to samples at the time of the study will be collected and processed using one of the software, namely SPSS 25. Based on the results of the analysis that has been carried out, it shows that brand trust and celebrity endorsers have a simultaneous effect on purchasing decisions. Brand trust has an effect on purchasing decisions. Celebrity endorser has an effect on purchasing decisions. The better the brand trust and celebrity endorser, the better it is for consumers to make a purchase decision. Keywords : Brand Trust, Celebrity Endorser, Purchase Decision